Financial centres in Europe : a new positioning in the global financial market post-crisis - Ayadi, Rym; Arbak, Emrah; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Assesses to what extent increased international cooperation could help selected financial centres in Europe respond to the future risks and opportunities facing them. The book identifies challenges that the jurisdictions face in coming years by means of representative samples and systematic comparisons of financial centres.
Keywords: Business; Accounting; Bookkeeping; Business enterprises -- Finance; Finance; Facility management; Behavioral economics; Macroeconomics